2020
DOI: 10.1099/jgv.0.001382
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma as antiviral therapy – effect on human herpes simplex virus type 1

Abstract: In previous studies, cold atmospheric plasma (CAP) was explored as an antibacterial and antiviral agent for the treatment of chronic wounds. The aim of the present study was to investigate whether CAP may also be suitable as an antiviral therapy against herpes simplex virus type 1 (HSV-1). HSV-1 most frequently manifests as recurrent herpes labialis, but it can also cause encephalitis, conjunctivitis or herpes neonatorum as a perinatal infection. HSV-1 encoding the reporter gene GFP was propagated. The CAP dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
0
23
0
2
Order By: Relevance
“…Consideration that acyclovir acts in PR 18,29,30 as well as in Herpes Labial with the same mechanism of action and effect, 31,32 and that the amino acid L‐lysine has similar results to acyclovir, 19,20 it is suggested that L‐lysine can act positively in PR.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration that acyclovir acts in PR 18,29,30 as well as in Herpes Labial with the same mechanism of action and effect, 31,32 and that the amino acid L‐lysine has similar results to acyclovir, 19,20 it is suggested that L‐lysine can act positively in PR.…”
Section: Discussionmentioning
confidence: 99%
“…For HSV-1 virus production, a previously described bacterial artificial chromosome (BAC) containing the HSV-1 genome was used to rescue the GFP tagged virus as previously described [ 53 ] and stored as a stock at −80 °C. The HSV-1 transduction efficiency was tested with incrementally increasing virus dosages and measured via flow cytometry analyses (Navios Flow Cytometer, Beckmann Coulter, Krefeld, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For HSV-1 virus production, a previously described bacterial artificial chromosome (BAC) containing the HSV-1 genome was used to rescue the GFP tagged virus as previously described [53] and stored as a stock at −80 • C. The HSV-1 transduction efficiency was tested with incrementally increasing virus dosages and measured via flow cytometry analyses (Navios Flow Cytometer, Beckmann Coulter, Krefeld, Germany). Vero cells were cultured in Dulbecco's Modified Eagle's Medium (DMEM, PAN-Biotech GmbH, Aiden-bach, Germany) supplemented with 10% fetal bovine serum (FBS, PAN-Biotech GmbH, Aidenbach, Germany) and 1% penicillin/streptomycin (PAN-Biotech GmbH, Aidenbach, Germany).…”
Section: Modified Heparin Tested On Hsv-1mentioning
confidence: 99%
“…This change was less perceptible concerning GFP expression levels 24 h after infection, which was in strong divergence to the acyclovir-treated (positive control), in which the viral load decreased from 95 to 25%. Briefly, a slight but measurable antiviral effect of LTP on HSV-1 was observed [25].…”
Section: Ltp To Treat Viruses' Infectionsmentioning
confidence: 99%
“…Plasma medicine applications include treatment of oral biofilm-related infections [12,13], treatment of wounds and skin diseases [19][20][21], assistance in cancer treatment [22][23][24], treatment of viruses infections (e.g. herpes simplex [25]); as well as, but not limited to, optimization of implants surfaces [26][27][28]. Each of those applications will be discussed in this review article ( Fig.…”
Section: Introductionmentioning
confidence: 99%